Influence of high temperature annealing on positron annihilation in electro-irradiated silicon; Physica status solidi (a); Vol. 47, Iss. 2 - Arefyev (Afef'ev, Arefiev) K. P. Konstantin Petrovich (1978, 1978)
В фонде НТБ ТПУ отсутствует